Maritime Security Strategy In Facing Illegal Fishing In Riau Province Indonesia - Tamarell Vimy Salsa Bila; Surya Wiranto; Rudiyanto; Pujo Widodo; Herlina Juni Risma Saragih; Panji Suwarno (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Riau Province has the potential of abundant marine resources, thus placing Riau in a maritime threat, especially illegal fishing which causes the country to suffer losses. This happens because this marine potential has not been utilized optimally so that it is exploited by foreign fishermen. This study will discuss the strategy of the Department of Maritime Affairs and Fisheries (DKP) of Riau Province to eradicate illegal fishing in Riau seas. The research argument is to involve local communities, improve human resources and technical skills, carry out patrols. The method in this research is descriptive qualitative research, with data collection techniques, namely interviews with DKP Riau Province, and literature studies, with the aim of knowing the right strategies in dealing with illegal fishing in Riau Province in supporting maritime security. This study reveals that the strategy needed is to increase the number of human resources and infrastructure for monitoring seas. Optimizing Community Monitoring Groups (Pokmaswas) which are social institutions by involving coastal communities and fishermen in assisting the government to safeguard and prevent threats to Indonesia's marine resources, enforce strict laws, and increase marine patrols.